Venture Capital Contracts: A Survey of the Recent Literature - Andrea Schertler (Kiel Institute of World Economics (IfW), 2000)
This paper surveys empirical and theoretical studies of various control mechanisms embedded in venture capital contracts. These mechanisms mitigate incentive problems and opportunistic behavior arising in the uncertain environment of financing young hightechnology enterprises that predominantly invest in intangible assets. In particular, the paper discusses the entrepreneurs' compensation, the type of financing, the staging of capital infusions, and various control rights explicitly given to venture capitalists. While theoretical studies explain some of the mechanisms empirically observed, others and the combinations of control mechanisms often used are still unexplained.
Keywords: D82; G32; G24; L14; 330; venture capital contracts; stage financing; convertible securities; entrepreneurs' compensation; Risikokapital; Unternehmensgründung; Finanzierung; Leistungsanreiz; Vertrag; Anreizvertrag; Agency Theory; Theorie